Analisis Transformasi Bahasa Gaul dalam Komentar Tiktok Unggahan @iniganta - Windi Putri Lestari; Risnawaty Risnawaty (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
. This research analyses the transformation of slang among Indonesian youth, particularly on the TikTok platform, as an indicator of shifts in communication and cultural trends. Using a qualitative approach and content analysis, this study focuses on the use of slang in TikTok comments to understand the meaning and context of frequently used terms. We randomly collected data from comments made by TikTok users who actively use slang. The analysis results show that the term "Btw" serves as an opener for a new conversation, "Ultah" is an abbreviation for "Ulang Tahun" (Birthday), "Candu" expresses a deep liking, and "Gemoy" describes something cute or adorable. The use of these terms reflects the rapidly evolving dynamics of language among the younger generation, showing how slang strengthens social interactions in the digital media. This research is expected to provide insights into the mindset and expressions of language speakers on social media, as well as encourage discussions on the preservation of the Indonesian language in the digital era.